The Influence of Marketing Skills on Work Achievement Through Interpersonal Skills in Companies - Abdulharis Tamalene; Nicoline Hiariej (International Journal of Economics (IJEC), 2023)
Marketing skills are a very valuable asset in the competitive business world. Strong marketing skills have a significant impact on achieving company goals. This includes several important capabilities, including communication skills, the ability to analyze markets, and a deep understanding of consumer behavior. Employees who have strong marketing skills have a greater tendency to achieve their sales targets and build strong relationships with their customers. Effective communication is one of the key elements of marketing skills. The ability to communicate clearly and persuasively, both orally and in writing, allows marketing professionals to communicate the value of their products or services in a compelling way. It also helps in building strong relationships with clients, which is often the deciding factor in maintaining business and achieving long-term success. It is also important to understand market data and analyze market trends, as this helps in designing the right strategy to reach the target market. Meanwhile, interpersonal skills are the key to success in modern business. This includes effective communication skills, the ability to work in a team, negotiation skills, empathy, and the ability to resolve conflicts. Employees who have strong interpersonal skills tend to be more successful in achieving their goals and feel satisfied with their work environment. This is critical in facing challenges in a rapidly changing business. Therefore, this research underlines the importance of developing marketing and interpersonal skills for employees in a competitive business environment. These skills not only benefit the individual but also have a positive impact on the entire organization. By better understanding the relationship between these skills and job performance, companies can direct their efforts to achieve success in an ever-changing marketplace. Additionally, this article highlights the need to invest in employee training to develop these skills.